IMPLEMENTASI ISO 8583 UNTUK HOST TO HOST MAHASISWABINA SARANA INFORMATIKA MELALUI CHANNELBILLER PT. FINNET INDONESIA BERBASIS AIX - Rahmat Tri Yunandar (Swabumi, 2016)
Bina Sarana Informatika is one of the public academic in Indonesia that already cooperated with FinnetIndonesia to handle the students Online Billing. So far Finnet have already provided channel transactionsto handle its Online Billing. The Development of other channel transaction will have been improving theservice of Online Billing transaction for BSI student. At this Final Task, the developement of Banking SMSchannel is done by implementing the ISO 8583 for connecting the BSI Online Billing System, with theDelima points channel. Moreover, its Banking SMS channel is also supported by the sender Aplication ofSMS based on Android mobile, that developed for helping the user or customer, by no need to rememberthe format of SMS for BSI Online Billing transaction. The system was developed by using the waterfallmodel process and Integration Testing method. Its Banking SMS channel that developed can help thecustomer for doing the transaction of BSIOnline Billing eficientlly in case of time, space, and velocity.